Exploratory Analysis of Related Factors with Absenteeism and Presenteeism on Workers: Using the Fourth Korea Working Condition Survey - Young-Hyeon Bae (MDPI AG, 2021)
Purpose: This study aimed to identify the factors related to absenteeism and presenteeism in workers and to provide basic evidence to help improve their quality of life and work productivity. Methods: Data from the Fourth Korea working condition survey were analyzed. A stepwise regression model was developed to identify the related factors for exploratory analysis. Results: Absenteeism and subjective risk perception related to work and health conditions were the strongest predictive factors, followed by presenteeism. Fatigue was the strongest predictive factor for presenteeism, followed by a high temperature at the workplace, lower back pain, and other health conditions, in that order. Conclusion: The quality of life and the productivity of workers could be improved by focusing on the factors affecting absenteeism and presenteeism, such as the working environment and health status.